PENGARUH PESAN DAKWAN PROGRAM “KAJIAN BERSAMA USTADZ” RADIO HIDAYAH 103,4 FM TERHADAP PENGETAHUAN ILMU AGAM ISLAM PADA MASYARAKAT KOTA PEKANBARU - Diena Nurul Haq; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Da'wah to God is the most noble and principal position for a servant, then it will not happen except with science. Da'wah is built on three basic principles, namely, Akidah, Syariat and Akhlak. The mass media conveys its messages to a wide and unlimited audience. Basically mass communication reveals the reaction resulted from the stimulus which in this case is given by the mass media. There is a close connection between media messages with the reaction or response of the audience. The S-R theory suggests that media messages containing the stimulus produce different responses from the audience. The purpose of this study is to find out how much influence the message preaching program